Evaluation of the Social Interaction in the Opening Spaces in the New Housing Project (Sulaimani City as a Case Study) - Ali, Alan Fraidoon (Sulaimani Journal for Engineering Sciences, 2014)
This research study the evaluation of open spaces in housing projects in Sulaimani city , threw an analytical study for the vertical and mixed housing projects and comparing with the planning and design standards for open spaces and its effect on social intercommunication and reaction , especially after the increasing of the numbers of housing units and projects and the increasing of the need for these projects and the encouraging of (KRG) and local government for vertical housing projects .Thus the planning and design of the housing projects were differently deals with the areas of open spaces , that’s for the research studies the open spaces and green areas in housing projects and its effect on social reaction and the level of these projects . In theoretical part the research study the understood of opens paces and the factors the effect on social reaction and , In practical part the research study the vertical housing projects in sulaimani city and the level of social reaction, the study conclude that the housing projects in Sulaimany city deals with the open spaces in different ways and the levels of social reaction are different because of the investment policies and the non-completed of the city master plan, depending on the factor of attracting clients in these projects .